Differential MicroRNA Expression Between Gastric Cancer Tissue and Non-cancerous Gastric Mucosa According to Helicobacter pylori Status - Lee, Jung Won (J Cancer Prev, 2017)
BACKGROUND: MicroRNAs (miRNAs) are key post-translational mechanisms which can regulate gene expression in gastric carcinogenesis. To identify miRNAs responsible for gastric carcinogenesis, we compared expression levels of miRNAs between gastric cancer tissue and non-cancerous gastric mucosa according to Helicobacter pylori status. METHODS: Total RNA was extracted from the cancerous regions of formalin-fixed, paraffin-embedded tissues of H. pylori-positive (n = 8) or H. pylori-negative (n = 8) patients with an intestinal type of gastric cancer. RNA expression was analyzed using a 3,523 miRNA profiling microarray based on the Sanger miRBase. Validation analysis was performed using TaqMan miRNA assays for biopsy samples from 107 patients consisted of control and gastric cancer with or without H. pylori. And then, expression levels of miRNAs were compared according to subgroups. RESULTS: A total of 156 miRNAs in the aberrant miRNA profiles across the miRNA microarray showed differential expression (at least a 2-fold change, P < 0.05) in cancer tissue, compared to noncancerous mucosa in both of H. pylori-negative and -positive samples. After 10 promising miRNAs were selected, validations by TaqMan miRNA assays confirmed that two miRNAs (hsa-miR-135b-5p and hsa-miR-196a-5p) were significantly increased and one miRNA (hsa-miR-145-5p) decreased in cancer tissue compared to non-cancerous gastric mucosa at H. pylori-negative group. For H. pylori-positive group, three miRNAs (hsa-miR-18a-5p, hsa-miR-135b-5p, and hsa-miR-196a-5p) were increased in cancer tissue. hsa-miR-135b-5p and hsa-miR-196a-5p were increased in gastric cancer in both of H. pylori-negative and -positive. CONCLUSIONS: miRNA expression of the gastric cancer implies that different but partially common gastric cancer carcinogenic mechanisms might exist according to H. pylori status.